4 - Revitalising Higher Education for Africa’s Future - Ebrima Sall; Ibrahim Oanda (Journal of Higher Education in Africa, 2014)
Over the last two decades, funding pressures have forced reforms in the legal framework of public universities in Africa. ‘Acts of Parliament’ and strong government direct control that dominated governance regimes of higher education institutions have given way to broad-based councils with wide representation in university governance organs. The strong emergence of private higher education institutions in the continent has led to the development of alternative forms of institutional management different from those that previously dominated in public institutions. But most of these reforms have resulted in new governance concerns revolving around financing and management, quality of teaching and research, and institutional autonomy. Prompted by the implications of these new concerns, guided by a strong belief that governance frameworks should respect institutional autonomy and institutional management, and that tenets of shared governance are critical to building quality higher education systems in Africa, CODESRIA launched a number of research networks to document governance reforms so far undertaken and to determine how they are reshaping the mission of higher education institutions on the continent. This article provides a synthesis of the findings emerging from the various research networks.